Microstructure and Mechanical Properties of Austenitic Compacted Cast Iron with Additive Manganese - K. M., Ahmad; Mohd Rashidi, Maarof; M., Ishak; M. S., Huzairi (EDP Sciences, 2015, 2016)
High composition of austenitic matrix in microstructure is contributed to its special characteristic in reducing cracking and distortion. This special alloy will be in austenitic matrix when high temperature and also at room temperature which make it successful avoid matrix volume changes. In this study, austenitic compacted iron with minimum nickel contain of 12wt% is produced by using in-mould magnesium treatment. Magnesium Ferro Silicon (MgFeSi) used in determining the graphite form. Some of nickel replace by manganese in range of 9wt% to 12wt% Mn while Nickel remain at 12wt% Ni at all parameter. This research focuses on to investigate the effect of alloying elements on microstructure and mechanical properties. The outcome compared to standard of unmodified austenitic cast iron as in ASTM standard. The matrix obtained was all in austenitic matrix with the presence of compacted graphite distribution throughout the matrix. It is appeared that result shows increment of manganese at the centre region between graphite in the microstructure. It is occurred when percentage of manganese addition was increased. There are increases in hardness compared to unmodified austenitic iron. Tensile strength decreases when the manganese content increases in alloy.